Adsorption Capacity and Desorption Efficiency of Activated Carbon for Odors from Medical Waste - Jung Eun Park; Eun Seo Jo; Gi Bbum Lee; Sang Eun Lee; Bum-Ui Hong (Molecules, 2023)
Five types of odor-emitting exhaust gases from medical waste were selected, and their adsorption capacity and desorption efficiency were investigated using activated carbon. The selected gases included polar gases (hydrogen sulfide (H2S) and ammonia (NH3)) and non-polar gases (acetaldehyde (AA), methyl mercaptan (MM), and trimethylamine (TMA))). Commercial activated carbon with a specific surface area of 2276 m2/g was used as the adsorbent. For the removal of odor from medical waste, we investigated: (1) the effective adsorption capacity of a single gas (<1 ppm), (2) the effect of the adsorbed NH3 gas concentration and flow rate, and (3) the desorption rate using NH3 gas. The values of the effective adsorption capacity of the single gas were in the following order: H2S < NH3 < AA < MM < TMA, at 0.2, 4.2, 6.3, 6.6, and 35.7 mg/g, respectively. The results indicate that polar gases have a lower effective adsorption capacity than that of non-polar gases, and that the size of the gas molecules and effective adsorption capacity exhibit a proportional relationship. The effective adsorption performance of NH3 gas showed an increasing trend with NH3 concentration. Therefore, securing optimal conditions for adsorption/desorption is imperative for the highly efficient removal of odor from medical waste.